Bridging the Gap to Communicate Abstract Concept of Physics for Visual Learners - Purnama Esa Dora Tedjokoesoemo (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
In vitruvius principles, a successful applied design should comply with 3 basic needs. Those are venusity (aesthetic), utilities (function), and firmities (structure). As the bones of the building, structures are often unseen, covered, and considered last by most interior design students. Columns and beams are often taken as a nuisance in creating the perfect canvas of blank space ready to design. Thus, it creates a fragmentation within the building development process to create a well performing building. Conventional approach to deliver the understanding and basics of physics in construction classes had struggled long before google image and pinterest came to flood the students with visual information in decorative manners. The presence of covid 19 then forced the construction teachers to think of appropriate teaching methods to keep increasing interest in learning on this less desirable subject. This study was conducted in a quantitative experimental method in 4 consecutive years of construction and statics class. This study aimed to review different delivery approaches and students' responses resembled through their performance in exam question assessment. The results of the study show that the students get better understanding by carrying out flip class methods because of the flexibility and discussion chances it has offered. However, the presented material should be equipped with graphics to help students to visualize.